Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1186/s13287-020-01638-2
|View full text |Cite
|
Sign up to set email alerts
|

PF-127 hydrogel plus sodium ascorbyl phosphate improves Wharton’s jelly mesenchymal stem cell-mediated skin wound healing in mice

Abstract: Background: Factors such as poor engraftment, retention, and survival of the transplanted stem cells are deemed to limit their therapeutic efficacy for wound regeneration. Hence, it is necessary to explore these issues in order to resolve them. In this study, we aim to investigate the role of Pluronic F-127 (PF-127) hydrogel plus antioxidant sodium ascorbyl phosphate (SAP) in enhancing Wharton's jelly mesenchymal stem cell (WJMSC)-mediated effectiveness on full-thickness skin wound healing in mice. Methods: Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 63 publications
3
20
0
Order By: Relevance
“…The WJMSCs were isolated from human umbilical cord and identified as our previous study report [ 21 ]. The WJMSCs were seeded in 90% DMEM/F12 media with 10% fetal bovine serum (FBS) and 1% penicillin/streptomycin (Gibco, Grand Island, NY) at 37 °C in an incubator with 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The WJMSCs were isolated from human umbilical cord and identified as our previous study report [ 21 ]. The WJMSCs were seeded in 90% DMEM/F12 media with 10% fetal bovine serum (FBS) and 1% penicillin/streptomycin (Gibco, Grand Island, NY) at 37 °C in an incubator with 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…In order to reduce the toxicity of PF-127 to WJMSC, recent studies have showed that adding membrane-stabilizing agent steroid hydrocortisone and platelet-rich plasma can significantly increase MSCs survival in PF-127 [ 19 , 20 ]. In addition, our previous studies have shown that sodium ascorbyl phosphate (SAP) can greatly enhance the viability of WJMSCs carried by PF127 and promote skin wound healing in mice [ 21 ]. SAP is the sodium salt of ascorbic acid 2-phosphate which has high stability even on after long-term exposure to reactive oxygen species as well as aqueous solution [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“… 37 In addition, the combination of the Pluronic F-127 hydrogel and Wharton’s jelly mesenchymal stem cells has been shown to have enhanced wound healing potential through potential M2 macrophage formation and enhanced angiogenesis. 38 Murphy et al demonstrated that the MSC spheroid-encapsulated fibrin hydrogel accelerated wound healing by enhanced secretion of bioactive factors to promote neovascularization and modulate the inflammatory milieu. 39 These results and ours suggested that combination therapy can provide a potential way for chronic wound treatment with high quality.…”
Section: Discussionmentioning
confidence: 99%
“…Mesenchymal stem cells Collagen-Fibrin [22], CH-GP-HEC [25], PHEMA-APMA-PAMAM [45], L-PDMA-PNIPAAm [46], PEG-PNIPAAm [26], Alginate [23], PEGDA [49], Fibrin [34], Gelatin-HA [27], PPS-b-PDMA-b-PNIPAAm [30], Alginate-Gelatin [16], PEG-4MAL-IFN-γ [53], HA-MAP [18,40] Bone marrow mesenchymal stem cells PNIPAAm-PHEMA-AOLA-PEGMA-PFO [33], CS-MA-PEGDA [24], Alginate-g-PNIPAAm [21] Wharton's jelly mesenchymal stem cells Poloxamer 407-SAP [50] BMP-2 transduced bone marrow mesenchymal stem cells GelMA [20] Brain-derived neurotrophic factor-producing mesenchymal stem cells Alginate (ultrahigh viscous) [42] Adipose-derived stem cells Gelan gum-HA [15], Poloxamer 407 [51], Gelan gum [43], PNIPAAm-SWCNTs [39], Alginate [19], PEG [17] Telomerase-immortalized human adipose-derived stem cells Gelatin-Methacrylamide [29] Cardiosphere-derived cells PNIPAAm [35], PNIPAAm-PPAA-PHEMA-OTMC-PEGMA [36] Human cardiac stem cells PNIPAAm-PAA [37] Neural stem cells-dental pulp stem cells Alginate-Collagen [47], CS-MA [48] Induced pluripotent stem cell-derived neural progenitor cells CS-bFGF [32] Human embryonic stem cell derived-neural stem cells HA [44] Retinal stem cell-derived rods and neural stem and progenitor cells HA and methylecelluse [41] Table 2. Cont.…”
Section: Stem Cell Type Biomaterialsmentioning
confidence: 99%
“…In the same manner, Deng et al investigated whether the combination of Pluronic F-127 with sodium ascorbyl phosphate as encapsulating biomaterials could affect the survival and healing properties of Wharton's jelly MSCs (WJMSCs) in an animal model of skin wound healing. Indeed, mice that received encapsulated WJMSCs inside Pluronic F-127 and sodium ascorbyl phosphate showed increased healing rates when compared to either non-encapsulated WJMSCs, Pluronic F-127-alone or sodium ascorbyl phosphate-alone encapsulated WJMSCs, as their dermis thickened, the number of hair follicles increased and the scarring decreased [50]. In another study, using alginate as the encapsulating biomaterial, Khatab et al showed that after the intra-articular injection of MSCs into the knee joints of rats, the survival rates of encapsulated MSCs were significantly higher compared to non-encapsulated cells.…”
Section: Improved Cell Viability and Proliferationmentioning
confidence: 99%